PBL13 Is a Serine/Threonine Protein Kinase That Negatively Regulates Arabidopsis Immune Responses . Issue 4 (2nd October 2015) - Lin, Zuh-Jyh Daniel; Liebrand, Thomas W.H.; Yadeta, Koste A.; Coaker, Gitta
Abstract : An Arabidopsis kinase possesses a unique repeat motif and suppresses resistance to the bacterial pathogen Pseudomonas syringae. Abstract: Receptor-like cytoplasmic kinases (RLCKs) are a subset of plant receptor-like kinases lacking both extracellular and transmembrane domains. Some of the 46 members in the Arabidopsis ( Arabidopsis thaliana ) RLCK subfamily VII have been linked to plant innate immunity; however, most remain uncharacterized. Thus, multiple subfamily VII members are expected to be involved in plant immune signaling. Here, we investigate the role of AvrPphB SUSCEPTIBLE1-LIKE13 (PBL13), a subfamily VII RLCK with unique domain architecture. Unlike other characterized RLCKs, PBL13 transfer DNA insertion lines exhibit enhanced disease resistance after inoculation with virulent Pseudomonas syringae . The pbl13-2 knockout also exhibits elevated basal-level expression of the PATHOGENESIS-RELATED GENE1 defense marker gene, enhanced reactive oxygen species (ROS ) burst in response to perception of bacterial microbial patterns, and accelerated flagellin-induced activation of mitogen-activated protein kinases. Recombinant PBL13 is an active kinase, and its primary autophosphorylated sites map to a 15-amino acid repeat motif unique to PBL13. Complementation of pbl13-2 with PBL13-3xFLAG converts the enhanced resistance and elevated ROS phenotypes back to wild-type levels. In contrast, kinase-dead PBL13 K111A -3xFLAG was unable to rescue pbl13-2 disease phenotypes. Consistent with the enhanced ROS burst in the pbl13-2 knockout, PBL13 is able to associate with the nicotinamide adenine dinucleotide phosphate, reduced oxidase RESPIRATORY BURST OXIDASE HOMOLOG PROTEIN D (RBOHD) by split-luciferase complementation assay, and this association is disrupted by flagellin treatment. We conclude that the PBL13 kinase negatively regulates plant innate immunity to pathogenic bacteria and can associate with RBOHD before pathogen perception. These data are consistent with the hypothesis that PBL13 acts to prevent inappropriate activation of defense responses in the absence of pathogen challenge.